(untitled) (The Conference Hub, 2025)
Childhood is considered the most innocent and dream-filled period of a person’s life. However, not every individual experiences childhood in the same way. For some, it is a source of sweet memories, while for others, it remains a time filled with hardships and injustices. Sadriddin Ayniy’s novel "Odina" is one of the most significant works that depict such bitter realities. This article analyzes the theme of childhood as portrayed in the novel "Odina."